Paclitaxel With Local Photothermal Therapy For Improved EMT6 Anticancer Strategy - Muhammad Redza, Mohd Radzi; Khairunadwa, Jemon (Universiti Teknologi Malaysia, 2021)
Paclitaxel (PTX), a highly hydrophobic chemotherapeutic drug has been reported to cause adverse reactions for example, systemic toxicity. Hence, combine strategy of PTX with phototherapy (HT) has been proposed as an alternative to reduce its dosage while increasing its efficacy. EMT6 cells were inoculated in Balb/c mice and treated with PTX and HT 7 days post-inoculation. Tumor growth and median survival of mice was tracked. The results revealed that PTX-HT mice experienced slower tumor progression and increased median survival. Thus, this data suggested that the proposed treatment enhance breast tumor regression and subsequently prolonged patients median survival.